Broken promises of marriage in early eighteenth-century Norway - Anne-Sofie Schjøtner Skaar (Sjuttonhundratal)
In early modern Norway, the engagement was by law binding and many people were in this period subjected to prosecution for breaking a promise of marriage. This article sheds light on the agency of women seeking justice for broken promises of marriage in early eighteenth-century Norway – a period in which the legislation and judicial practice in such cases was at its strictest – exemplified with a specific case-study from Northern Trøndelag. The case concerned two people from the upper echelon of society, Margrete Bull and Christian Rosenkrantz, and is in some ways a typical example of how such matters could be handled in court in this period. According to Margrete, Christian had given her a promise of marriage and made her pregnant, but Christian denied both the engagement and the fatherhood and moreover married another woman of higher standing. In a period of four years, from 1707 to 1711, the case was addressed multiple times in the local court, the Chapter Court (Kapittelrett) and finally in the Supreme Court of Denmark-Norway. In the end, Margrete Bull was the victorious party and was awarded with a sizable compensation. In line with previous research on the topic, this case demonstrates the importance of honor and local support, but moreover indicates that only those in possession of sufficient resources could take a trial to the level presented here.